Indirect hemagglutination assay for diagnosis of Escherichia coli O157 infection in patients with hemolytic-uremic syndrome. - Bitzan, M (1992)
An indirect hemagglutination assay consisting of sheep erythrocytes coated with lipopolysaccharide (LPS) from Shiga-like toxin-producing Escherichia coli O157 was used for the serological diagnosis of E. coli O157 infections in children with classical (enteropathic) hemolytic-uremic syndrome (HUS). One week after the onset of diarrhea (acute phase of the disease), the E. coli O157 antibody titer was greater than or equal to 1:4,096 in 22 of 27 patients with HUS, compared with 4 of 249 controls, the majority of whom had O157 antibody titers of between 1:4 and 1:256. This antibody response was observed in HUS patients with stool cultures positive and negative for E. coli O157. Selective absorption with homologous LPS and heterologous LPS showed that the antibody response was specific for E. coli O157. Because of its simplicity and ease of interpretation, the indirect hemagglutination assay described in this paper is recommended for the serological diagnosis of E. coli O157 infections in patients with HUS.